Penggunaan Teknologi informasi Dalam Meningkatkan Produktivitas Industri - Tio Ramadan; Anas Nurrahman; Cahya vallenio (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In facing increasingly competitive business competition today, the development of information technology has a huge impact on company competitiveness. In order for companies to be competitive, companies must continuously follow developments and advances in information technology. One of the advantages of a company's competitiveness is using economic criteria with measures of effectiveness, efficiency and productivity. The aim of applying information technology for companies is to obtain a value chain from information technology that is useful in all aspects of business which is oriented towards increasing the effectiveness, efficiency and productivity of employees and companies to obtain targeted margins with minimal risk and costs.